Implementasi FingerPrint dan Short Message Service Gateway pada Sistem Presensi - Purnomo , Rakhmat; Fudholi, Ahmad (Jurnal Kajian Ilmiah, 2020)
The research aims to apply the fingerprint and Short Message Service technology in the attendance system. Presence or attendance is an important activity in the lecturing process. SMK Global Teknologi has a problem in the student attendance data. The human error factor in captured student attendance is a problem in itself. On the other hand, there are cases of students who went to school but did not arrive at school to become complaints from parents. Fingerprint technology has been proven to be able to validate someone as proof of attendance, while the SMS gateway is proven to be a reliable telecommunications technology for data communication. The research method used was to conduct observations at the SMK Global Technologi. The interview method was carried out with the principal, representatives of parents, teachers, and students. The system development method used is Waterfall which consists of the stages of planning, analysis, design, finally implementation. The testing method used a black-box. The results of the research are the application of student attendance information systems with an attendance system indicator that has been integrated between parents, teachers, homeroom teachers. So that student attendance data can be directly known. Keywords: Attendance System, Fingerprint, SMS Gateway Abstrak Tujuan penelitian ini untuk menerapkan teknologi fingerprint dan Short Message Service (SMS) dalam sistem presensi. Presensi atau kehadiran merupakan kegiatan yang penting dalam proses pembelajaran. SMK Global Teknologi memiliki masalah dalam data presensi siswanya. Faktor kesalahan manusia dalam merekap kehadiran siswa menjadi masalah tersendiri. Disisi lain adanya kasus peserta didik yang berangkat ke sekolah tetapi tidak sampai kesekolah menjadi keluhan orang tua. Teknologi fingerprint telah terbukti dapat memvalidasi seseorang sebagai bukti kehadiran, sedangkan SMS gateway terbukti untuk sebagai teknologi telekomunikasi yang handal untuk komunikasi data. Metode penelitian yang digunakan adalah dengan melakuan observasi di SMK Global Teknologi. Metode wawancara dilakukan kepada kepala sekolah, perwakilan orang tua, guru, dan siswa. Metode pengembangan sistem yang digunakan adalah Waterfall yang terdiri dari tahapan perencanaan, analisis, perancangan, dan penerapan. Metode pengujian menggunakan black-box. Hasil dari penelitian ini adalah diterapkannya sistem informasi kehadiran peserta didik dengan indikator sistem kehadiran sudah terintegrasi antara orang tua, guru, wali kelas. Sehingga data kehadiran siswa dapat secara langsung diketahui. Kata kunci: Sistem Kehadiran, Fingerprint, SMS Gateway